(untitled) (Research, Society and Development, 2022)
Studies from different countries verified the relationship between deterioration of quality of mental health and academic engagement decrease of college students during pandemic period of COVID-19. This study aim to describe indicators of academic engagement, anxiety, academic anxiety, and social skills (SK) of college students during COVID-19 context. Participants were 88 college students of different semesters of a undergaduate course of Psychology from the interior of State of São Paulo. Data were collected in 2020 by an online questionnaire. Main results indicated: a) participants of the 7th semester achieved greater mean of academic engagement, academic anxiety and SK; and participants of the 5th semester achieved the lower mean oh the same indicators; b) statistics correlations between SK categories and academic engagement; SK categories and academic anxiety categories. Final considerations suggest the results corroborate the literature on damage to mental health in college students as a result of coping with the pandemic.